Hoodoo - Smith, Ronald L. (Ronald Lenard), 1959- (Clarion Books, Houghton Mifflin Harcourt, 2015)
In 1930s Alabama, twelve-year-old Hoodoo Hatcher is the only member of his family who seems unable to practice folk magic, but when a mysterious man called the Stranger puts the entire town at risk from his black magic, Hoodoo must learn to conjure to defeat him.